The Introduction of Cost Sharing for Prescription drugs: Evidence from The Irish Longitudinal Study of Ageing (TILDA) - Mohan, Gretta; Nolan, Anne; Moriarty, Frank (The Economic and Social Review, 2021)
Ageing populations and age-related morbidity present major challenges for advanced economies in managing rapidly increasing pharmaceutical expenditures. However, older people, particularly those with low incomes, may be susceptible to negative effects from cost sharing for medicines. The impact of introducing prescription drug co-payments for older publicly-insured patients (medical cardholders) in Ireland using data from The Irish Longitudinal Study on Ageing is explored. Descriptive evidence revealed that medicines use increased despite the imposition of small co-payments for medical cardholders relative to trends for private patients. However, features of the Irish market must be taken into account in interpreting this counterintuitive result.